2013
DOI: 10.1016/j.ntt.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and genetic manipulations of folate metabolism differentially affect neocortical functions in mice

Abstract: Converging evidence suggests that folate-mediated one-carbon metabolism may modulate cognitive functioning throughout the lifespan, but few studies have directly tested this hypothesis. This study examined the separate and combined effects of dietary and genetic manipulations of folate metabolism on neocortical functions in mice, modeling a common genetic variant in the MTHFD1 gene in humans. Mutant (Mthfd1gt/+) and wildtype (WT) male mice were assigned to a folate sufficient or deficient diet at weaning and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 86 publications
(104 reference statements)
3
6
0
Order By: Relevance
“…We did not measure metabolites in these pathways in the brain, but in liver we observed that betaine concentrations were decreased. This is consistent with previous observation that Mthfd1 gt/+ mice have reduced expression of the choline dehydrogenase (Chdh) gene compared to WT mice [16]; CHDH converts choline to betaine [20]. Betaine is important because of its role as a methyl donor and as an osmoregulator [21].…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…We did not measure metabolites in these pathways in the brain, but in liver we observed that betaine concentrations were decreased. This is consistent with previous observation that Mthfd1 gt/+ mice have reduced expression of the choline dehydrogenase (Chdh) gene compared to WT mice [16]; CHDH converts choline to betaine [20]. Betaine is important because of its role as a methyl donor and as an osmoregulator [21].…”
Section: Introductionsupporting
confidence: 93%
“…When the genders were analyzed separately, there was no difference between female mice, but we observed a trend towards decreased response (p = 0.06) in male mice (data not shown). This trend is in concordance with previously published reports describing behavioral impairments in male Mthfd1 gt/+ mice [16]. The Mthfd1 gt/+ mice did not show other behavioral abnormalities in any of the remaining behavioral tests, summarized in Table 1.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…2B). The observation of increased folate and MTHFD1 enrichment in the nucleus during folate deficiency provides a mechanism that accounts for the lack of a neural tube defect phenotype in Mthfd1 gt/ϩ mice and why these mice are protected from uracil accumulation in DNA and exhibit marked impairments in homocysteine remethylation (15,30,31).…”
Section: Discussionmentioning
confidence: 99%